Error analysis in algebra learning: Exploring misconceptions and cognitive levels - Mathaba, Philile Nobuhle; Bayaga, Anass; Tîrnovan, Daniela; Bossé, Michael J. (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
This research investigates errors and misconceptions among learners in algebraic education by utilizing Koch's error analysis method alongside the Structure of the Observed Learning Outcome (SOLO) taxonomy. The primary aim of the investigation is to discern the kinds of errors and cognitive stages demonstrated by Grade 9 students when engaged in algebraic problem-solving tasks. The studies' outcomes uncover several prevalent error categories, including conjoining, cancellation, and problem-solving errors, indicating deficiencies in conceptual comprehension and procedural execution. Moreover, applying the SOLO taxonomy elucidates learners' diverse levels of understanding, with a majority position within the uni-structural or multi-structural stages. Theoretical implications underscore the necessity for tailored instructional approaches to mitigate learners' obstacles and foster a deeper grasp of algebraic principles. Consequently, this research contributes significantly to the advancement of algebraic pedagogy and provides valuable insights for curriculum enhancement, thereby facilitating improved mathematics learning outcomes.